Pengembangan Flashcard Digital untuk Meningkatkan Penguasaan dan Pemahaman Kosakata Siswa Kelas II Sekolah Dasar - Shafira Dini, Faza; Zainuddin, Almuntaqo (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
This study aims to develop digital flashcard learning media to enhance vocabulary understanding and mastery among second-grade students at SD Negeri Kertonatan 01. The development model used is ADDIE, which consists of five stages: analysis, design, development, implementation, and evaluation. The media was designed using Canva and converted to the Heyzine.com website with added vocabulary audio. Validation was carried out by media and material experts to assess the feasibility of the media, followed by trials involving teachers and seven students. The research findings indicate that the digital flashcards are feasible and reasonably effective for learning. Media expert validation resulted in a score of 74.6%, while material expert validation reached 78%, both categorized as "Feasible." Trial results with teachers and students yielded 90% and 85.3%, respectively, categorized as "Highly Feasible." The effectiveness test demonstrated an improvement in students' understanding, with an average N-Gain score of 0.68 and an effectiveness percentage of 68%, categorized as "Moderately Effective." Thus, these digital flashcards can assist students in better understanding and mastering vocabulary. The use of this media offers an interactive and innovative learning experience, making it a viable alternative for vocabulary learning in elementary schools.